Isolation and detection of enteroinvasive Escherichia coli from skewered meatballs by using ipaH gene - Restiani, R. (2023)
Nowadays, food safety has become an increasingly important aspect to be considered, particularly in developing countries such as Indonesia. Yogyakarta is known for its plethora of street foods, which are sold in public places and school environments. In the present work, the microbiological safety of such street foods, particularly skewered meatballs, was assessed. The present work aimed to detect enteropathogenic bacterial contaminations, particularly enteroinvasive E. coli (EIEC), using a combination of microbiological, biochemical assay API 20E, and molecular characterisation of virulence factor by ipaH primer pairs. The results confirmed the presence of bacterial contamination particularly from the most-common coliform group. The street food vendors must be educated by presenting information that the total bacterial count has exceeded the safety threshold. The microbiological examination confirmed the presence of suspected enteropathogenic colonies, based on the biochemical assays. Molecular identification of three isolates yielded positive results containing ipaH gene, which is a strong indication of EIEC-type of bacteria, most probably E. coli and Shigella spp.